The Implementation of Interactive Media for Learning in Blended Learning on Business Ethics - Santoso, A; Lestari, S; Susilowati, N; ., Tusyanah (KnE Social Sciences, 2018)
The objectives of this research were; (1) to know the implementation of interactive media in blended learning on Business Ethics at Faculty of Economics UNNES to improve students” ethical knowledge; and (2) to know the implementation of interactive media in blended learning on Business Ethics to improve students’ generic skills. It was a quasi-experimental research approach with static group comparison design. There were an experimental class and a control class. Then, data were processed and analyzed by using descriptive analysis and inferential analysis (independent sample t test). The results of the study showed that (1) there were differences in student learning outcomes between control class and experimental class at Business Ethics; (2) from various skills in generic skills, blended learning was able to improve learning mastery on ICT, numeracy, work organization, problem solving and cooperation. Furthermore; blended learning stimulates students learn independently through social media; either facebook or blog since lecturers provided materials and also practiced questions in groups through social media, then the results were also sent via e-mail. Keywords: Interactive Media For Learning, Blended Learning, Business Ethics Knowledge, Generic Skills, Accounting Education Students